Question-based Writing Process: A Reflection and a Proposal to L2 Writing - Ruth Angela Ortiz (Asociación Colombiana de Profesores de Ingles, 2017)
This article focuses on the problem of writing as it has been traditionally approached without reference to the learners' interests and expectations. Also, due to the fact that it demands considerable time and effort it has been regarded as homework. Due to this, compositions include a series of problems that show that learners rely on their native language. As a result of this, their writings lack coherence and cohesion. To minimize this problem a question-based writing process is suggested. This is based on referential and display questions, as these have been found to be of value in provoking ideas. This particular situation is interesting in that it elicits the writer's own ideas and feelings. Thus, when students answer their questions they become aware of the value of the answers in the thoughtful organization of their writings.